2011
DOI: 10.1002/aenm.201100172
|View full text |Cite
|
Sign up to set email alerts
|

Open‐Cage Fullerenes as n‐Type Materials in Organic Photovoltaics: Relevance of Frontier Energy Levels, Carrier Mobility and Morphology of Different Sizable Open‐Cage Fullerenes with Power Conversion Efficiency in Devices

Abstract: Organic bulk heterojunction (OBHJ) photovoltaics, incorporating open‐cage fullerenes with orifice‐size of 8, 12, 13, 16 and 20‐membered‐rings as n‐type materials, display power conversion efficiency (PCE) up to 2.9% by the 8‐membered‐ring fullerene under AM 1.5G irradiation; their PCEs decrease as the orifice‐size of open‐cage fullerene increases, primarily due to electron‐mobility descends as the cage is ruptured to larger holes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Redox potentials of the compounds were measured by cyclic voltammetry (CV) in CH 2 Cl 2 in the presence of Bu 4 NPF 6 as as upportinge lectrolyte and calibrated versusf errocenium/ferrocene (Fc + /Fc). [24] Furthermore, the reversible reduction processes of indandione derivative 7b are cathodically shifted versus potentials of 7a to À1.12, and À1.49 V, which implies that reduction is more feasible in less electron-rich 7a.T he more pronounced modulation of electron density in A-p-A compounds was achieved upon substitution of the boryl core with strongly electron-accepting DCIND substituents. Molecule 7a bearing two dicyanomethylene groups undergoes two reversible reduction processes at À1.00 and À1.25 V. These potentials are comparable to the reduction potentials of ac ore-unsubstituted perylenebisimide (À0.95, À1.15 V) whichw as successfully applied as an n-type semiconducting material, [23] and correspond well with the position of the LUMO of fullerenes (À3.8 to À4.3 eV).…”
Section: Electrochemistrymentioning
confidence: 99%
“…Redox potentials of the compounds were measured by cyclic voltammetry (CV) in CH 2 Cl 2 in the presence of Bu 4 NPF 6 as as upportinge lectrolyte and calibrated versusf errocenium/ferrocene (Fc + /Fc). [24] Furthermore, the reversible reduction processes of indandione derivative 7b are cathodically shifted versus potentials of 7a to À1.12, and À1.49 V, which implies that reduction is more feasible in less electron-rich 7a.T he more pronounced modulation of electron density in A-p-A compounds was achieved upon substitution of the boryl core with strongly electron-accepting DCIND substituents. Molecule 7a bearing two dicyanomethylene groups undergoes two reversible reduction processes at À1.00 and À1.25 V. These potentials are comparable to the reduction potentials of ac ore-unsubstituted perylenebisimide (À0.95, À1.15 V) whichw as successfully applied as an n-type semiconducting material, [23] and correspond well with the position of the LUMO of fullerenes (À3.8 to À4.3 eV).…”
Section: Electrochemistrymentioning
confidence: 99%
“…In 1992, Sariciftci et al [29] firstly reported that C 60 could efficiently quench MEH-PPV emissions by photoinduced electron transfer from the excited state of a conducting polymer onto buckminsterfullerene, C 60 , and related phenomena are not limited to MEH-PPV. After that, different structures of fullerene and its derivatives with various energy level alignment were doped into the polymer for high efficiently photoinduced electron transfer from the excited state of organic semiconducting materials [30][31][32][33][34][35][36][37]. These fullerene derivatives have many advantages in photovoltaic cells, including a deep-lying LUMO (~3.8-4.2 eV) for effective charge separation between the electron donor and acceptor, reversible reduction with ability to accept up to six electrons, ultra-fast three dimensional charge transfer, and high electron mobility.…”
Section: Electron Withdrawing Semiconducting Materialsmentioning
confidence: 99%
“…A series of fullerene derivatives with different diameter cage from C 70 to C 84 were used as electron acceptors in bulk heterojunction polymer-fullerene solar cells [32][33][34][35][36][37]. These fullerene derivatives have many advantages in photovoltaic cells, including a deep-lying lowest unoccupied molecular orbital (LUMO, ~3.8-4.2 eV) for the effective charge separation between the electron donor and acceptor, reversible reduction with ability to accept up to six electrons, ultra-fast three dimensional charge transfer, and high electron mobility.…”
Section: Electron Withdrawing Semiconducting Materialsmentioning
confidence: 99%
See 2 more Smart Citations